Breathing Life Into the Stone Fort Treaty - Craft, Aimee (Purich Publishing, 2011)
This dissertation will demonstrate that, by considering Treaty One (1871) from the perspective of the Anishinabe, especially Anishinabe laws or Anishinabe inaakonigwein and normative expectations, one can obtain a better understanding of why there is a discrepancy in interpretations of the treaty. The research draws on practices of treaty making prior to Treaty One and shows that the parties relied extensively on Anishinabe protocols and procedural laws in the context of the Treaty One negotiations. In addition, kinship relationships, the obligations derived from them, and a sense of the sacred obligations involved in treaty-making, informed the agreement that was made between the parties. In particular, the kinship between a mother and child was invoked by the parties; the Crown negotiators relying on it primarily to secure good terms with the Anishinabe and the Anishinabe advocating for a commitment to ensuring a good life while respecting and preserving their autonomy. The exploration of the historical records of the negotiations and the oral history surrounding the treaty help draw out the differing and sometimes competing understandings of the treaty, many of which continue to this day, and in particular in relation to the effect of the treaty agreement on legal relationships to land. They help illuminate questions regarding the interpretation of the Treaty, including what would be necessary in order to implement it in accordance with its signatories’ understandings. Graduate 0398, 0740